Implementasi Penyusunan Lesson Plan Berbasis Multiple Intelligences Research Di Mi Muhammadiyah Pk Kartasura - Azzahra, Ulya Dewi; , Murfiah Dewi Wulandari, S.Psi.,M.Psi Psikolog (2017)
This study aimed to describe 1.) Implementation Plan Lesson preparation based Research in Multiple Intelligences MI Muhammadiyah PK Kartasura. 2) Barriers to Implementation Plan Lesson preparation based Research in Multiple Intelligences MI Muhammadiyah PK Kartasura 3.) solution in preparation of the Implementation of Multiple Intelligences Lesson Plan based Research in MI Muhammadiyah PK Kartasura. This type of research is qualitative. The main informants of this research is classroom teachers 2A, 2B and 2C are additional informants school supervision (Guardian Angel) and the principal. Data collection techniques used were interviews, documentation and observation. Data were analyzed through the steps of data reduction, data presentation and conclusion. Mechanical data validity checking is done degan triangulation. The results showed that in MI Muhammadiyah PK Kartasura has implemented Lesson Plan Implementation preparation based Multiple Intelligences Research with both having stage 1) Introduction of student intelligence conducted through hasi MIR 2) preparation of Multiple Intelligences Lesson Plan based Research consists of Header ( identity and syllabus), Component activity (preliminary (alpha zone), the core activities (exploration, elaboration and confirmation), Cover (assessment, validation). 3.) Consult seklah supervision. Although there are obstacles, but the teacher has given a solution so that these obstacles can both be minimized